(untitled) (American Journal of Islam and Society, 2014)
This sociological study on the plural and often contested construction of Muslim identities in Brazil contributes to a growing scholarship on Islam and the politics of religious difference across the Atlantic. Focusing on two institutions in São Paulo state – the Islamic Center of Campinas (Centro Islâmico de Campinas) and the Islamic Charity Youth League of Brazil (Liga da Juventude Islâmica Beneficente do Brasil), located in the Brás neighborhood of São Paulo city – Cristina Maria de Castro’s book frames the negotiation of what it means to be Muslim in Brazil and in the wider ummah not only with regard to the historical longue durée and plural religious field, but also in terms of gender and ethnic politics. By focusing on this “range and diversity of [an] Islamic diaspora,”1 to use the words of Gayatri Spivak, this book will help “undo the politically monolithized view of Islam that rules the globe today.” Based on a doctoral dissertation at the Federal University of São Carlos (UFSCar, São Paulo state) and post-doctoral research at the International Institute for the Study of Islam in the Modern World (Leiden University), Castro’s work also speaks to the increasing internationalization of the Brazilian social sciences. During the twentieth century, many sociologists, anthropologists, and others in Brazil were limited by what Andrew Wimmer and Nina Glick-Schiller have criticized as “methodological nationalism,” namely, car- rying out their research within the nation’s boundaries.2 Now based at the Federal University of Minas Gerais, Castro studied Islam in Brazil with regard to not only the transnational networks, imagined or otherwise, of two Muslim institutions located in São Paulo state, but also the equally far-flung circulation of orientalist, Islamophobic images that members of these and ...